European values in numbers : trends and traditions at the turn of the century - Luijkx, Ruud. (European Values Studies, 2016)
This volume presents the beliefs and values of people in European countries and the trends that appeared at turn of the century. Based on survey data from the 1981, 1990, 1999, and 2008 values studies in Europe, trends in human values are examined concerning important life domains such as religion and morality, primary relations and family life, work and leisure time, society and political culture. It shows the cultural varieties and similarities in value profiles of the Europeans at the end of the 20th and beginning of the 21st century.